Substitution of agar agar by Isabgol (Plantago ovate) and Sago (Metaxylon sago) for preparing myceological culture media - Das, Nilanjana; Mahapatra, S C; Chattopadhyay, R N (Mushroom Research, 2015)
Please see the full text